KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - NOR, TAUFIK; SURIANSYAH, AHMAD (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
This study aims to analyze the role of visionary leadership of school principals in improving the quality of education. Visionary leadership is a leadership style that is oriented towards achieving a long-term vision through innovation, collaboration, and proactive change management. A qualitative approach with a case study design was used to explore the practice of visionary leadership in schools. Data were obtained through in-depth interviews, observations, and document analysis involving principals, teachers, students, and parents as informants. The results of the study indicate that visionary principals have a clear and communicative vision, are able to encourage learning innovation, and create a collaborative organizational culture. The implementation of visionary leadership strategies has a significant impact on improving student learning outcomes, teacher professionalism, and school resource management. However, obstacles such as resistance to change, limited facilities, and lack of leadership training are challenges that must be overcome. In addition, this study reveals that the success of visionary leadership is greatly influenced by support from teachers, staff, parents, and government policies. This study concludes that visionary leadership is the key to improving the quality of education through targeted and sustainable organizational change. With adequate support, principals can become effective agents of change, creating adaptive and innovative schools in accordance with the demands of the times. The results of this study are expected to be a reference for the development of educational leadership in the future. ABSTRAKPenelitian ini bertujuan untuk menganalisis peran kepemimpinan visioner kepala sekolah dalam meningkatkan mutu pendidikan. Kepemimpinan visioner merupakan gaya kepemimpinan yang berorientasi pada pencapaian visi jangka panjang melalui inovasi, kolaborasi, dan pengelolaan perubahan secara proaktif. Pendekatan kualitatif dengan desain studi kasus digunakan untuk menggali praktik kepemimpinan visioner di sekolah. Data diperoleh melalui wawancara mendalam, observasi, dan analisis dokumen dengan melibatkan kepala sekolah, guru, siswa, dan orang tua sebagai informan. Hasil penelitian menunjukkan bahwa kepala sekolah visioner memiliki visi yang jelas dan komunikatif, mampu mendorong inovasi pembelajaran, serta menciptakan budaya organisasi yang kolaboratif. Implementasi strategi kepemimpinan visioner berdampak signifikan pada peningkatan hasil belajar siswa, profesionalisme guru, dan pengelolaan sumber daya sekolah. Namun, hambatan seperti resistensi terhadap perubahan, keterbatasan fasilitas, dan kurangnya pelatihan kepemimpinan menjadi tantangan yang harus diatasi. Selain itu, penelitian ini mengungkap bahwa keberhasilan kepemimpinan visioner sangat dipengaruhi oleh dukungan dari guru, staf, orang tua, dan kebijakan pemerintah. Penelitian ini menyimpulkan bahwa kepemimpinan visioner merupakan kunci dalam meningkatkan mutu pendidikan melalui perubahan organisasi yang terarah dan berkelanjutan. Dengan dukungan yang memadai, kepala sekolah dapat menjadi agen perubahan yang efektif, menciptakan sekolah yang adaptif dan inovatif sesuai dengan tuntutan zaman. Hasil penelitian ini diharapkan dapat menjadi referensi bagi pengembangan kepemimpinan pendidikan di masa depan.